Out of Africa? A dated molecular phylogeny of the cicada tribe Platypleurini Schmidt (Hemiptera: Cicadidae), with a focus on African genera and the genus Platypleura Amyot & Audinet‐Serville. (29th March 2019) - Price, Benjamin W.; Marshall, David C.; Barker, Nigel P.; Simon, Chris; Villet, Martin H.
Abstract: The Platypleurini is a large group of charismatic cicadas distributed from Cape Agulhas in South Africa, through tropical Africa, Madagascar, India and eastern Asia to Japan, with generic diversity concentrated in equatorial and southern Africa. This distribution suggests the possibility of a Gondwanan origin and dispersal to eastern Asia from Africa or India. We used a four‐gene (three mitochondrial) molecular dataset, fossil calibrations and molecular clock information to explore the phylogenetic relationships of the platypleurine cicadas and the timing and geography of their diversification. The earliest splits in the tribe were found to separate forest genera in Madagascar and equatorial Africa from the main radiation, and all of the Asian/Indian species sampled formed a younger clade nested well within the African taxa. The tribe appears to have diversified during the Cenozoic, beginning c . 50–32 Ma, with most extant African lineages originating in the Miocene or later, well after the breakup of the Gondwanan landmass. Biogeographical analysis suggests an African origin for the tribe and a single dispersal event founding the Asian platypleurines, although additional taxon sampling and genetic data will be needed to confirm this pattern because key nodes in the tree are still weakly supported. Two Platypleurini genera from Madagascar ( Pycna Amyot & Audinet‐Serville, Yanga Distant) are found to have originated by late Miocene dispersal of a single lineage from Africa. The genus Platypleura is recovered as polyphyletic, with Platypleura signifera Walker from South Africa and many Asian/Indian species apparently requiring assignment to different genera, and a new Platypleura concept is proposed with the synonymization of Azanicada Villetsyn.n. The genera Orapa Distant and Hamza Distant, currently listed within separate tribes but suspected of platypleurine affinity, are nested deeply within the Platypleurini radiation. The tribe Orapinisyn.n . is here synonymized while the tribe Hamzini is pending a decision of the ICZN to preserve nomenclatorial stability. Abstract : The first molecular assessment of the African and Asian cicada tribes Hamzini, Orapini and Platypleurini shows Orapa and Hamza nested deeply within the Platypleurini radiation. The tribe Orapinisyn.n. is a junior synonym of the tribe Platypleurini, while Azanicada syn.n. is synonymized with Platypleura and Platypleura zuluensis stat. rev. reassigned. The tribe has an African origin with subsequent dispersal in the Miocene to Asia following the collision of Africa and Asia, and with oceanic dispersal to Madagascar.